Building Customers’ Trust in the Banking Sector of Sokoto State, Nigeria - Bello Bada, Abdulrahman; Karupiah, Premalatha (School of Social Science, 2014)

(untitled)
Customers’ patronage in relation to banking sector, the use of its products and services are manifesting constant challenges for assessment of trust. Trust strongly depends on the level of improvement and banking commitment to customer satisfaction. However, trust is tied to some associated important dimensions which are: dispositional, institutional and interpersonal. Therefore, this article tends to highlight the need for management and policy makers in the banking sector to identify and understand the important of all the dimensions stated above in building customers’ trust on bank, its products and services. Further, this paper recommend the need for executive members of the banking sector to use any of the identified dimensions that strongly influence or predicts customers’ trust on banking sector to improve influential strategies for banking products and services.